Saudi Arabia's sustainable tourism development model: New empirical insights. Issue 239 (5th March 2021) - Iswan,; Khan, Aqeel; Kadir, Firdaus Khairi Abdul; Jabor, Mohd Khata; Anis, Siti Nisrin Mohd; Zaman, Khalid
Abstract: The study extended the conventional Autoregressive Distributed Lag (ARDL) model into the lead model, supported with a partial adjustment model and adaptive expectation model. The ARDL‐LEAD modelling is applied to Saudi Arabia's tourism industry to assess the country's environmental sustainability agenda (ESA) by using monthly time series data from 1995M01‐2018M12. The short‐run results confirmed the Environmental Kuznets Curve (EKC) hypothesis with the lag variables, while the U‐shaped relationship was found between economic growth (EG) and CO2 emissions with the leads variable. The inbound tourism and trade openness (TOP) decrease CO2 emissions at the lead factor in the short‐run. The long‐run relationship verified the U‐shaped relationship between EG and CO2 emissions, while TOP openness increases CO2 emissions to substantiate 'pollution haven hypothesis (PHH)' in a country. The Wald Granger causality shows the different variations at the current period and forecasted estimates. The Granger estimates at the current level confirmed the growth‐led emissions (GLE), tourism‐led emissions (TLE), and tourism‐led growth (TLG) hypotheses, while at forecast estimates, the results substantiate the TLE and emissions‐led growth (ELD) hypotheses in a country.